2018
DOI: 10.21909/sp.2018.01.749
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive and Social Sources of Adolescent Well-being: Mediating Role of School Belonging

Abstract: The aim of the study was to explore direct a nd indirect pa thwa ys from cognitive factors (academic and social self-perception) to adolescent well-being through school belonging. The direct and indirect effects of cognitive factors were investigated on both concurrent and prospective well-being indicators. The first data collection was held in the beginning of the school year, the study sample consisted of 139 freshmen of three high schools in Nitra (53 boys, 86 girls, M age = 15.63, SD = 1.15). The second da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…Social relations, higher social support, and a sense of community, even online (Facebook), contributed to decreased loneliness and increased happiness [ 109 , 110 , 111 ]. School belonging mediated the association between social and academic competence and students’ concurrent happiness [ 112 ]. However, a study found no significant relationship between social support and happiness [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Social relations, higher social support, and a sense of community, even online (Facebook), contributed to decreased loneliness and increased happiness [ 109 , 110 , 111 ]. School belonging mediated the association between social and academic competence and students’ concurrent happiness [ 112 ]. However, a study found no significant relationship between social support and happiness [ 113 ].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, these relationships are bidirectional, with adolescents' perceptions of their relationship with other people and those people's perceptions of adolescents being important in establishing social connections. Previous studies suggested social connectedness as a central dimension in determining adolescent well-being and that the feelings of belonging and integration in the school social environment mediated the relationship between students' academic and social skills and dimensions of social connection, happiness, and optimism within well-being ( 20 , 21 ). Furthermore, other studies [e.g., ( 22 )] suggested that adolescents' low social connectedness within middle school social groups is positively associated with depressive and anxiety symptoms.…”
Section: Adolescents' Well-being: the Epoch Modelmentioning
confidence: 99%
“…The results presented by Lukoševičiute et al ( 24 ), in which 133 studies on the subjective happiness of adolescents were included, suggested that most studies [i.e., 64] used a single item to measure subjective happiness, and only 18 of them had validation procedures. However, adolescent happiness seems to be positively associated with social connectedness and optimism ( 21 ), highlighting its relevance for the optimal development of adolescents' well-being.…”
Section: Adolescents' Well-being: the Epoch Modelmentioning
confidence: 99%
“…Parr et al (2020) identified belonging as the largest known correlate with symptoms of depression, accounting for nearly 50% of its variance. Other research has found benefits for mental health and emotional well-being (Allen et al, 2018b;Arslan, 2018;Arslan et al, 2020;Li & Jiang, 2018;Šeboková et al, 2018;Zhang et al, 2018), academic success, hardiness, social inclusion, and life satisfaction (Abdollahi et al, 2020;Arslan et al, 2020;Brooms, 2016;Palikara et al, 2021;Scorgie & Forlin, 2019), self-esteem and associated positive outcomes (Foster et al, 2017;Peng et al, 2019), lowered school dropouts (Organisation for Economic Co-operation and Development [OECD], 2018;Uslu & Gizir, 2017), reduced likelihood of absenteeism, misconduct, school disengagement or students leaving school early without a qualification (Ibrahim & El Zaatari, 2019;Korpershoek et al, 2020;OECD, 2018), decreased feelings of alienation, isolation and disaffection or low social integration and social exclusion (Arslan et al, 2020;Palikara et al, 2021), and better performance and self-belief in abilities to succeed academically (Chun et al, 2016;Holloway-Friesen, 2019). Recent research shows that a sense of school belonging is a significant predictor of future employment, education, and training (NEET) (Parker et al, 2021), even up to 15 years post-school, and our understanding of the role that school belonging plays in the psychosocial adjustment of students who have experienced traumatic events or other forms of stress (Cardeli et al, 2020;Zhang et al, 2021) has immense implications for educational practice, as well as therapeutic benefits.…”
mentioning
confidence: 96%